1970
DOI: 10.1136/hrt.32.5.708
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous origin of left coronary artery from pulmonary artery associated with an aorto-pulmonary septal defect

Abstract: Aorto-pulmonary septal defects and anomalous origins of left coronary artery from pulmonary artery are briefly discussed. The difficulties of diagnosis and surgical correction are put forward in a situation when the left coronary artery arises from a site of high pressure and saturation, such as the pulmonary artery in the presence of an aorto-pulmonary septal defect, as in the case described.This report describes the clinical, haemodynamic, angiographic, and necropsy findings in an infant with anomalous origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1976
1976
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…3,9 Other associated anomalies include patent ductus arteriosus, coronary artery anomalies, ventricular septal defect, atrial septal defect, tetralogy of Fallot, and transposition of great arteries. [10][11][12] In a series of 42 pediatric cases of APW, 16 cases (38%) had associated patent ductus arteriosus. 11 APW with PDA first presenting in adult has been rarely reported in only one case report, to the best of our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…3,9 Other associated anomalies include patent ductus arteriosus, coronary artery anomalies, ventricular septal defect, atrial septal defect, tetralogy of Fallot, and transposition of great arteries. [10][11][12] In a series of 42 pediatric cases of APW, 16 cases (38%) had associated patent ductus arteriosus. 11 APW with PDA first presenting in adult has been rarely reported in only one case report, to the best of our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that coronary artery anomalies accompany 5-10% of cases (14,15). Diagnosis of these patients in the preoperative period may be challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Anomalous origin of the coronary arteries can occur in 5 to 10% of the cases of APW 30,31 . Pre-operative diagnosis is usually difficult due to the absence of clinical manifestations of ischemia, since a high perfusion pressure secondary to the APW leads to a good coronary artery flow.…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of associated lesions, its accuracy decreases 41 . APW should always be considered when the left atrium is very dilated or there is severe pulmonary hypertension 30 . The diagnosis by 2DE should be made by visualizing the aortopulmonary septum in two or more different planes.…”
Section: Discussionmentioning
confidence: 99%